Exploring hybridity the rise of "Cordilleran cinema" in the digital age - Dasalla, Jonnie Lyn P.; Deocampo, Nicolas A. (Quezon City University of the Philippines, Diliman, 2024)
The study explores how the rise of Igorot film productions in the digital age shapes the notion of “Cordilleran Cinema.” The democratization of digital technology advances the growth of local regional film productions, providing new perspectives and narratives from the indigenous community. This phenomenon alters the current landscape of Philippine Cinema, which is predominantly centralized in Metro Manila.

Through the lens of Homi Bhabha’s hybridity, the study examines the implication of the colonialists’ influence on the Igorot identity through the various processes of Cordilleran film productions. The ‘cultural circuit’ devised by Stuart Hall, Paul du Gay, and their colleagues was utilized to understand and analyze the representation, identity, and production process of Cordilleran film productions. Interviews with Cordilleran filmmakers and film festival organizers were conducted to provide insights into the local film practices. Ten (10) short films and eleven (11) full-length films produced by Cordilleran filmmakers were examined through textual analysis.

This study revealed common characteristics of Cordilleran films: culturally diverse, raw and authentic, embedded with cultural values, influenced by Christianization, and mostly community-based. The thesis proposes Cordilleran Cinema as a collective term for films produced by Cordilleran filmmakers featuring the Cordillera Region and its people. Five parameters were identified to consider in determining a Cordilleran film: geography, language, characters and actors, material and non-material culture, sensibility, and the filmmaker’s roots. However, the suggested definition and markers are not yet conclusive since Cordilleran Cinema’s characteristics continue to evolve through time. Future scholars are encouraged to engage in ongoing discourse and further studies to deepen our understanding of Cordilleran Cinema. This includes exploring topics such as audience reception, digital video con
Thesis
Keywords: Motion pictures -- History and criticism -- Philippines -- Cordillera Region; Digital media -- Social aspects -- Philippines